Students' perceptions on ethnic tolerance in Malaysia: A study in three public universities. (February 2021) - Wan Husin, Wan Norhasniah; Halim, Norhana Abdul; Zul Kernain, Nur Farahana
This study is an attempt to develop an index on ethnic tolerance among the Malay, Chinese and Indian undergraduate students of three Malaysian public universities. It focuses on three main domains: religious practices, ethnic‒cross relationship and governance. The data of 378 respondents were analyzed using the Statistical Package for the Social Science (SPSS) software version 22. The calculation and the measurement of the index are based on the method and equations used in calculating the index among Malaysian youths in 2015 that were capable of incorporating many domains. All the domains are significant in contributing to ethnic tolerance the composite index value of 4.13 out of 5 was obtained which shows the students are at the level of highly tolerant.